2019
DOI: 10.1097/hmr.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Women at the helm: Chief executive officer gender and patient experience in the hospital industry

Abstract: Background Health care scholars have recognized the important role leaders play in the improvement of health care delivery systems, yet few have explored the kind of leaders who make a difference or the conditions under which certain health care executives thrive. Recent work in the hospital industry suggests that the role of chief executive officer (CEO) gender may be particularly salient in the context of patient experience (Galstian, Hearld, O’Connor, & Borkowski, 2018). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Overall, the results of studies focusing on the relationship between gender and performance in both public and private organisations confirm a positive relationship between women's representation and performance (Sabharwal, 2014;Ostrup and Villadsen, 2015;Elwood and Garcia-Lacalle, 2015;Silvera and Clark, 2019;Cuadrado-Ballesteros et al, 2021), though some studies fail to support this claim or provide conflicting results depending on the contingent situation (Darmadi, 2013). With a few exceptions (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the results of studies focusing on the relationship between gender and performance in both public and private organisations confirm a positive relationship between women's representation and performance (Sabharwal, 2014;Ostrup and Villadsen, 2015;Elwood and Garcia-Lacalle, 2015;Silvera and Clark, 2019;Cuadrado-Ballesteros et al, 2021), though some studies fail to support this claim or provide conflicting results depending on the contingent situation (Darmadi, 2013). With a few exceptions (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to Silvera and Clark (2019), female CEOs improve the interpersonal care experience more quickly than male CEOs. Gender analysis at the middle management (health and administrative professionals) and staff level (nurses and other employees) in health organisations is lacking, though Arena et al (2021) focused on the influence of gender in the adoption of new technologies at the top and middle management levels.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent review of workforce diversity in human service organizations found that diversity is associated with enhanced creativity and innovation, improved workplace commitment, and increased retention (Mor Barak et al, 2016). There is considerable concern, however, regarding the scarcity of diversity in health care providers, executive leaders, and governance (ACHE, 2008;Dotson & Nuru-Jeter, 2012;Mitchell & Lassiter, 2006;Silvera & Clark, 2021;Smith, Nsiah-Kumi, Jones, & Pamies, 2009;Sullivan, 2004).…”
Section: Hudmentioning
confidence: 99%
“…In this vein, Ref. [41] found that female CEOs improve interpersonal care experience faster than male CEOs, particularly in the most complex executive job environments. It has been noted that women seem to fit better in this particular industry due to healthcare services' relational and interpersonal nature.…”
Section: Review Of the Literature And Hypothesismentioning
confidence: 99%